PIERRE BAYLE HISTORIEN DE LA PHILOSOPHIE: UN SONDAGE - ANTONY MCKENNA (Lexicon Philosophicum)
The critical tradition reduces Bayle’s philosophy to Pyrrhonism and avoids the analysis of his arguments by jumping to the conclusion that he aims to establish the uncertainty of all philosophical reasoning. This article aims to demonstrate that this interpretation of Bayle’s intention is erroneous: he is not Pyrrhonian in historiography and he is a staunch rationalist in the fields of ethics. In the Dictionary, he seems to trace a history of philosophy, but a close reading of his articles shows that he does not attempt to a establish a coherent and systematic history of philosophy. He does indeed demonstrate that philosophical systems fail when faced with certain problems (definition of space and time, for instance), but above all he pinpoints those problems over which reason is incompatible with the Christian doctrine. In other words, he does not aim to enumerate Pyrrhonian uncertainties but to attack rationalist theology from a variety angles: he thus seeks to demonstrate that Christian faith is irremediably irrational